The Perceive of Self and Peer Correction on the Improvement of Writing Ability, Critical Thinking and Students Learning Autonomy of Japanese Students - Saragih, Febi Ariani; Widanty, Dinda Surya (CV. Komunitas Dunia Peternakan, 2024)
This study aims to perceive student perceptions on self-correction and peer correction feed back to improve writing ability , student perceptions on self-correction and peer correction to increase autonomy learningof Japanese students. Self-Correction is an activity of providing indirect feedback where the teacher gives choices to students that allow them to carry out the correction activity themselves. Meanwhile, Peer Correction is a method that consists of learners giving and receiving feedback about their writing from their peers, that is, other learners. This research belongs to ex-post facto and survey research designs. Determination of the sample using random sampling technique using the Slovin formula. In this research, the research object was 42 Japanese Language Education students class of 2020 who had taken the Chukyuu Sakubun 1 course in semester 3. The data collection technique was carried out using a questionnaire and documentation in the form of students' Sakubun scores. The data is then processed quantitatively using t-Test SPSS software. The results of this study indicate that the value of the count test for the self-correction variable is 2.541 where this value is greater than the table value of 2.0108 and is significant at a significance level of 0.015, so it can be concluded that the self-correction variable has a significant effect on ability, critical thinking, and autonomy. The peer correction variable is 3,533 where this value is greater than the table value of 2.0108 and is significant at a significance level of 0.001, so it can be concluded that the peer correction variable has a significant effect on ability, critical thinking, and autonomy.